A Multi-Tracer Study of Fresh Water Sources for a Temperate Urbanized Coastal Bay (Southern Baltic Sea) - von Ahn, Cátia Milene Ehlert; Scholten, Jan C.; Malik, Christoph; Feldens, Peter; Liu, Bo; Dellwig, Olaf; Jenner, Anna-Kathrina; Papenmeier, Svenja; Schmiedinger, Iris; Zeller, Mary A.; Böttcher, Michael Ernst (Frontiers in Environmental Science, 2021)
Surface waters (SW) and submarine groundwater discharges (SGD) act as a source of fresh water and dissolved substances for coastal ecosystems. However, solute fluxes of SGD depend on the groundwater composition and the benthic water-solid-microbe interactions close to the sediment-water interface. This study aims to identify and evaluate the biogeochemical impact of different fresh water sources, focus on SGD, to Wismar Bay (WB), southern Baltic Sea, Germany. We are particularly interested in characterizing the mixing zones where SGD meets WB waters in the surface sediments, and in comparing these process to the ones from SW inputs. Moreover, we hypothesized that coastal anthropogenic activities promote the connection between coastal aquifers and the sea bottom. Sampling took place on transects through WB and the concentrations of dissolved inorganic carbon, nutrients, major ions and trace elements, stable (H, O, C, S), and radium (Ra) isotopes were analyzed. Geophysical acoustic techniques were applied to identify potential litho-morphological controls for SGD spots, as well as anthropogenic features. Sediment cores were retrieved for geochemical porewater and sediment analyses, and organic matter mineralization rates and element fluxes for the sediment-water interface were modeled. Additional samples comprise porewaters from the fresh-salt water mixing zone at the WB shore-line, as well as fresh surface and groundwaters near the study area WB were considered. Enhanced concentrations of dissolved manganese, barium and Ra in the SW of the eastern WB indicated benthic-pelagic coupling via exchange between porewater and the water column. Salinity and major ions in sediment porewater profiles identified the presence of fresh ground water below about 50 cmbsf in the central part of the bay. The sea bottom in the central bay is under impact of sediment excavation, shortening the interface layer between the coastal aquifer and the sea bottom. The porewater stable isotope composition (δ18O, δ2H) follows on the local meteoric water line indicating a relatively modern fresh ground water source, which is modified afterwards during transport in the subterranean estuary. The SGD flux is diffuse in this site, and the fresh/brackish water migration impact the elemental fluxes and the process taking place across the sediment-water interface.